Comparing the assimilation of dietary nitrogen supplied by animal-, plant- and microbial-derived ingredients in Pacific white shrimp Litopenaeus vannamei: A stable isotope study - Gamboa Delgado, Julián; Nieto López, Martha Guadalupe; Maldonado Muñiz, Maribel; Villarreal Cavazos, David Alonso; Tapia Salazar, Mireya; Cruz Suárez, Lucía Elizabeth (2020)
In order to become a more profitable and sustainable industry, the aquaculture sector is constantly exploring alternative nutrient sources. In the present study, the natural stable isotope signatures of different animal-, plantand microbial-derived ingredients were determined to evaluate the assimilation of dietary nitrogen in Pacific white shrimp. Experimental diets were manufactured to replace fish meal and squid meal with microbial- and plant- derived ingredients (48 and 66 % dietary inclusion) and were also used as additives (4%). Ingredients were also used as additives to study their effects on growth performance and assimilation. Corn gluten, soy protein isolate, Arthrospira (Spirulina) biomass and a bacterial meal (ProFloc™) were used to formulate six, isotopic control diets containing one source of dietary nitrogen, while six combined diets had varying proportions of ingredients. At the end of the trial, survival rates were similar among treatments (88 ± 9%) but there were significant differences in mean final weight. Microbial and animal proteins promoted similar final weight when combined (1080−1537 mg), while plant ingredients and Arthrospira caused lower growth when used alone (420−970 mg). Isotopic values indicated significant differences in the assimilation proportions of dietary nitrogen, mainly attributed to the ingredients’ different amino acid profiles. The dietary nitrogen contained in microbial-derived ingredients was assimilated at similar, or even higher proportions than fish meal and squid meal. Diet formulated with 33 % fish meal, Arthrospira and corn gluten, contributed 31, 36 and 33 % of dietary nitrogen to muscle growth, respectively. The second 33 % combination supplied 42, 34 and 24 % from squid meal, bacterial meal and soy protein. When ingredients were used at 4%, additive levels, they also contributed structural nitrogen to shrimp muscle tissue despite low dietary inclusions. Results demonstrated the viable use of stable isotopes to evaluate the assimilation of dietary nitrogen supplied by emerging alternative ingredients